The mechanisms of substrates interaction with the active site of Mycobacterium tuberculosis tyrosyl-tRNA synthetase studied by molecular dynamics simulations - Mykuliak, V.V.; Kornelyuk, A.I. (Вiopolymers and Cell, 2014)
Aim. To study the mechanisms of substrates interaction with the active site of Mycobacterium tuberculosis tyrosyl-tRNA synthetase (MtTyrRS). Methods. Complexes of MtTyrRS with tyrosine, ATP and tyrosyl adenylate were constructed by superposition of the MtTyrRS structure and crystallographic structures of bacterial TyrRS. All complexes of MtTyrRS with substrates were investigated by molecular dynamics (MD) simulations in solution. Results. It was shown the formation of network of hydrogen bonds between substrates and the MtTyrRS active center, which were stable in the course of MD simulations. ATP binds in the active site both by hydrogen bonds and via electrostatic interactions with Lys231 and Lys234 of catalytic KFGKS motif. Conclusions. The L-tyrosine binding site in the enzyme active site is negatively charged, whereas the ATP binding site contains positive Lys231 and Lys234 residues of catalytic KFGKS motif. The occupancy of H-bonds between substrates and the enzyme evidences a significant conformational mobility of the active site. Мета. Дослідити механізми взаємодії субстратів реакції аміноацилювання з активним центром тирозил-тРНК синтетази еубактерії Mycobacterium tuberculosis (MtTyrRS). Методи. Суперпозицією MtTyrRS з кристалографічними структурами бактерійних TyrRS побудовано комплекси з тирозином, тирозином, АТФ і тирозиладенілатом. Комплекси MtTyrRS з субстратами вивчали методом моделювання молекулярної динаміки (МД) у розчині. Результати. Показано водневі зв’язки між субстратами і активним центром MtTyrRS та їхню стабільність у процесі МД. Стабільність АТФ в активному центрі забезпечується водневими зв’язками, а також електростатичними взаємодіями з Lys231 та Lys 234 каталітичного мотиву KFGKS. Висновки. Ділянка зв’язування L-тирозину в активному центрі ферменту є негативно зарядженою, тоді як ділянка зв’язування АТФ має позитивно заряджені Lys231 і Lys234 каталітичної послідовності KFGKS. Процентне співвідношення тривалості існування водневих зв’язків, які формуються між субстратами та ферментом, до загального часу моделювання МД свідчить про конформаційну рухливість активного центра. Цель. Исследовать механизмы взаимодействия субстратов реакции аминоацилирования с активным центром тирозил-тРНК синтетазы эубактерии Mycobacterium tuberculosis (MtTyrRS). Методы. Суперпозицией MtTyrRS с кристаллографическими структурами бактериальных TyrRS построены комплексы с тирози- ном, тирозином и АТФ и тирозиладенилатом. Комплексы MtTyrRS с субстратами изучали методом симуляции молекулярной динамики (МД) в растворе. Результаты. Показаны водородные связи между субстратами и активным центром MtTyrRS и их стабильность в процессе МД. Стабильность АТФ в активном центре обеспечивается водородными связями, а также электростатическими взаимодействиями с Lys231 и Lys234 каталитического мотива KFGKS. Выводы. Сайт связывания L-тирозина в активном центре фермента заряжен отрицательно, в то время как участок связывания АТФ имеет положительные Lys231 и Lys234 каталитической последовательности KFGKS. Процентное соотношение длительности существования водородных связей, формирующихся между субстратами и ферментом, к общему времени моделирования МД свидетельствует о конформационной подвижности активного центра.